Sinkronisasi Ekonomi Pancasila Dan Ekonomi Islam - Muhammad Ali Akbar; Moh. Idil Ghufron (Universitas Muhammadiyah Surabaya, 2019)
AbstractThis study discusses the concept of Pancasila economics and Islamiceconomics which have basic and not conflicting similarities. Both of theseeconomic concepts share the goal of realizing social justice for allIndonesian people and social equality in prosperity and prosperity asstated in the five precepts of the Pancasila, as well as imbued with the firstprinciple of the One Godhead Pancasila as its basis.In this study also explained that between the Pancasila economicconcepts and Islamic economics are two economic concepts whose basicprinciples, characteristics and systems are in accordance with theteachings in the Qur'an which is the holy book of Muslims. So that this canstrengthen the confidence of the Indonesian people to not hesitate toimplement the Pancasila economy which is the noble heritage of thefounding fathers of the nation.The method used in this study is library research, which refers to primalmaterials from two components which are the subject of discussion,namely the study of Pancasila economics and Islamic economics. Andadded with other books relating to the problems studied. While the writingmethod used is descriptive analytical, namely by collecting actualinformation in detail and thoroughly from the data obtained, to thendescribe the exact problem under study, then analyze it directly to becompiled as needed in this study by using data content analysis analysis.Kata Kunci: Ekonomi, Pancasila, Islam, Al-Qur‟an, Keadilan,Kesejahteraan.